Distribution correlations of cadmium to calcium, phosphorus, sodium and chloridion in mangrove Aegiceras corniculatum root tissues. (January 2018) - Li, Jian; Yu, Junyi; Yan, Chongling; Du, Daolin; Liu, Jingchun; Lu, Haoliang
Abstract: Nutriment distributions might influence Cd distribution and Cd tolerance in mangrove plant roots. To demonstrate this, Aegiceras corniculatum was stressed by Cd, and the distributions of Cd, Ca, P, Na and Cl in plant roots were detected with the aid of SEM-EDX. It was found that endodermis, pith and xylem were the predominant tissues for retardation and regional enrichment of Cd. Na and Cl distributions suggest a critical role of salt resistance tissues on Cd tolerance in roots. P participated in Cd retardation and regional enrichment of endodermis and xylem. P, Na, Cl and Ca distribution had a high correlation to that of Cd in roots. The synergetic accumulation between Ca and Cd could be a crucial mechanism for Cd tolerance in A . corniculatum roots. In conclusion, the research of Cd and nutriment distributions in A . corniculatum roots deepens the understanding on Cd tolerance in mangrove plants. Highlights: Cd was mainly distributed in the endodermis, pith and xylem of A . corniculatum roots. Salt resistance tissues (endodermis) played a critical role on Cd tolerance of roots. P participated in the Cd retardation and regional enrichment of endodermis and xylem. Synergetic accumulation between Ca and Cd was a crucial mechanism for Cd tolerance.